Rainfall Erosion Damage of Residual Soil Slope in Intermittently Frozen Area Based on Discrete Element Method - Ke, Yunbin; Chen, Yanyu; Jiang, Zhenliang; Qiu, Yonghui (Frontiers in Materials, 2021)
This study developed a discrete element simulation model based on the 2D particle flow code (PFC2D), of which the mesoscopic parameters were calibrated by the indoor experiments, to investigate the rainfall erosion damage of residual soil slope in the intermittently frozen area. To be noted, the runoff scouring action was simulated according to the equivalent rainfall method, and the soil particles on the slope were given initial velocity, and the water absorption was considered by increasing the unit weight. The results indicated that the scouring action only caused superficial erosion with the main damage region at the foot, no matter the FT effect. A splitting phenomenon was observed in the lower part of the steeper slope under the FT effect. Moreover, no matter considering the FT effect, the gentler slope tends to occur a spalling rather than a splitting phenomenon, where the soil particles slid along the structural plane with strong anti-scouring ability. Besides, the gentler slope maintained higher stability and shorter scouring time. Finally, the scouring velocity increased the erosion damage to a large extent.